Plan de negocios para la creación de microempresa de artesanías del tejido en el cabildo indígena muisca de Bosa (2021)
The National Indigenous Organization of Colombia currently recognizes 102 indigenous peoples established around the country, representing 3.5% of the Colombian population. Their safeguards vary between hundreds and dozens of individuals who keep a significant history and worldview for the culture, which is worthy of preservation and empowerment.